Climate-Meteorological And Anthropogenic Influence On The Fall Of The Water Level In Lake Prespa - Violeta GJEŠOVSKA; Vasko STOJOV (Macedonian association of structural engineers-MASE, 2022)
R. N. Macedonia has more than 160 lakes. Fifty of them are natural. According to the way their basins were formed, the three largest natural lakes in the territory of the Republic of Macedonia, namely, Lake Ohrid, Lake Prespa and Lake Dojran, are of a tectonic type. A common feature of tectonic lakes is that they age naturally. The term aging means filling of their volume space with sediments as well as reduction of their water quantity and water level. The subject of this paper are the changes in the water level of Lake Prespa, manifested by large fluctuations in the past. The absolute maximum water level of Lake Prespa was registered on July 15, 1963, at an elevation of H = 851.83 m above the sea level (a.s.l.), while in August 2021, the level was at elevation H = 842.24 m a.s.l, which is the absolutely measured minimum. At such registered water levels, an amplitude of 959 cm is observed. The reasons for the decrease in the water level of the lake have not been clearly defined. There are numerous studies and papers that point out the causes and these are mainly located in the climatemeteorological changes and the increased anthropogenic effects. Through analysis of available information on climate-meteorological characteristics (air temperature, precipitation), hydrological data (change of water level in the lake) and information on the use of water from the lake, only at the measuring stations on the Macedonian side, for the period from 1951 to 2020, the water balance has been defined in order to identify the factors that are dominant and are the reason for the current state of the lake.
Keywords: Lake Prespa; Water level; Water balance; Precipitation; Air temperature.